Solute Transport in Bentonite Buffer Under Thermal Hydraulic Mechanical Coupling - Uy D. Vo; Mamadou Fall; Julio Á. I. Sedano; Maïwenn Humbezi-Desfeux; Jean-Michel Matray; Manuel Marcoux; Son T. Nguyen (Geotechnical and Geological Engineering, 2026)
This paper investigates solute transport processes in the bentonite buffer of a Deep Geological Repository (DGR) for used nuclear fuel, using the Canadian concept as an example. The design relies on a multi-barrier system in which the used fuel container (UFC) provides containment and the surrounding bentonite buffer protects the UFC while retarding radionuclide migration following a potential breach. Solute transport in the buffer is strongly influenced by coupled thermal-hydraulic-mechanical (THM) processes. A coupled THM-transport model was developed to evaluate (1) reactive transport of bisulfide $$\left({\text{H}\text{S}}^{-}\right)$$ HS - from the host rock to the UFC and associated UFC corrosion; and (2) radionuclide migration following a hypothetical UFC breach. The model builds on previous verification and validation and is further assessed against laboratory-scale bisulfide transport experiments and a large-scale thermal diffusion experiment at the Tournemire Underground Research Laboratory (France). The results show that temperature-dependent diffusion is the dominant transport mechanism, significantly enhancing solute migration, whereas hydraulic desaturation has limited influence and the Soret effect is negligible at repository scale. Under the reference conditions, adsorption and $$\text{F}\text{e}\text{S}$$ FeS precipitation delay detectable HS − flux to the UFC until approximately 5 × 10 5 years and limit the predicted corrosion depth to ~ 0.05 mm after one million years. In the breach scenario, the buffer effectively delays and attenuates moderately/strongly sorbing radionuclides (e.g., 135 Cs, 237 Np). The effectiveness in retarding radionuclides' migration is most sensitive to bentonite diffusivity and sorption capacity.

Multiphysical Modelling of Pile Behaviour Under Combined Vertical and Lateral Loads in Thermally Variable Soils - Shuang Chang; Mamadou Fall; Husham Almansour (Geotechnical and Geological Engineering, 2026)

Infectious Diseases Management in Small‐Scale Freshwater Aquaculture in West Africa: Lessons for Low‐ and Middle‐Income Countries - Mame Boucar Diouf; Robane Faye; Ahou Rachel Koumi; Nounagnon Darius Tossavi; Enoutchy Fabrice Bouah; Ephigénie Ndew Dione; El Hadji Malick Sy Camara; Kadjo Henri Joel Niamien; Ué Clavier Zéa Bi; Atto Delphin Kouadio; El Hadji Papa Abdourahim Sy; Thérèse Adeline Fatou Gomis; et al. (Reviews in Aquaculture, 2026)
Infectious diseases are an increasing threat to food security, small‐scale livelihoods and the sustainability of aquaculture in low‐ and middle‐income countries (LMICs). In sub‐Saharan Africa, aquaculture is expanding rapidly but production systems often remain fragile. In West Africa, particularly in Benin, Côte d'Ivoire and Senegal, production remains modest despite rising demand. Interactions between farming practices, environmental exposures (e.g., contaminants and agricultural effluents) and pathogen emergence are poorly documented. Here we review evidence on production systems, reported pathogens, diagnostic and surveillance capacity in these three countries. We find that (i) production relies mainly on small‐scale ponds, cages often within integrated agro‐aquaculture systems with recurring constraints in biosecurity, water management and governance; (ii) available evidence is fragmented and uneven across pathogen groups, with most reports focusing on bacterial and parasitic conditions and major gaps for viruses, fungi, co‐infections, antimicrobial resistance and combined environmental pressures; and (iii) health management and laboratory capacities remain constrained, but existing networks and experience from terrestrial animal health provide entry points for integrated and participatory surveillance. We discuss these patterns through an exposome‐informed One Health lens, highlighting how multiple exposure pathways link farms, watersheds and nearby communities. Based on this synthesis, we outline research and policy priorities to strengthen health resilience and to support more sustainable small‐scale freshwater aquaculture in West Africa and, with relevance to other tropical LMIC settings.

Flow ability of cemented paste backfill with high-volume industrial wastes - Qianlong Li; Mamadou Fall (Minerals Engineering, 2026)

Consolidation behavior and shear strength characteristics of polymer-paste tailings barrier - Chinaza C. Paul; Mamadou Fall (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Shear behavior of two-order asperities in three-dimensional rock joints: Experimental investigation and development of a morphology-based shear strength criterion - Qinkuan Hou; Shuhong Wang; Mamadou Fall; Rui Yong; Meaza Girma (Engineering Geology, 2025)

Coupled chemo-mechanical modeling of early-age pastefill material under cyclic loading - Ailing Li; Mamadou Fall; Gongda Lu (Computers and Geotechnics, 2025)

Numerical simulation of solute transport in argillaceous rock under thermal gradient with a coupled THM-solute transport model - Uy Vo; Mamadou Fall; Julio Ángel Infante Sedano; Maïwenn Humbezi-Desfeux; Jean-Michel Matray; Manuel Marcoux; Thanh Son Nguyen (Geomechanics for Energy and the Environment, 2025)

Flow characteristics of paste tailings in surface disposal: the role of pyrite content - Oyewale Miracle; Mamadou Fall; Alireza Ghirian (Environmental Science and Pollution Research, 2025)

Physical Modeling of the Geotechnical Behaviour of Cemented Backfill Plug with and Without Nanoparticles Under Simulated Field Overburden Pressure - Amirreza Saremi; Mamadou Fall (Geotechnical and Geological Engineering, 2025)

Investigating Pore Water Pressure Development in Paste Backfill Under Conditions Mimicking Field Loading - Zubaida Al-Moselly; Mamadou Fall (Geotechnical and Geological Engineering, 2024)

Column experiments to study the thermo-hydro-mechanical-chemical behavior of sensitive marine slay subgrade soil treated with lime - Chanda Tunono; Mamadou Fall (Bulletin of Engineering Geology and the Environment, 2024)

THMC Behavior of Lime-Stabilized Clay Subgrade Under Daily Thermal Cycles: Column Experiments - Chanda Tunono; Mamadou Fall (Geotechnical and Geological Engineering, 2024)

Characteristics of fracture changes and fatigue failure signals for siltstone under cyclic loading - Hui Wang; Mamadou Fall; Shengjun Miao (International Journal of Rock Mechanics and Mining Sciences, 2024)

Strength development and self-desiccation of saline cemented paste backfill - Elizabeth Alexandra Carnogursky; Mamadou Fall; Sada Haruna (Environmental Science and Pollution Research, 2024)

Rheology and setting time of saline cemented paste backfill - Elizabeth Alexandra Carnogursky; Mamadou Fall; Sada Haruna (Minerals Engineering, 2023)

Blast response of cantilever retaining wall: Modes of wall movement - Najlaa Abdul-Hussain; Mamadou Fall; Murat Saatcioglu (Transportation Geotechnics, 2023)

Pollution assessment around a big city in West Africa reveals high concentrations of microplastics and microbiologic contamination - Amidou Sonko; Patrice Brehmer; Guillaume Constantin de Magny; Gaël Le Pennec; Bissoume Sambe Ba; Ousmane Diankha; Mamadou Fall; Isabelle Linossier; Maryvonne Henry; Issa N’Diaye; Saliou Faye; Yoba Kande; et al. (Regional Studies in Marine Science, 2023)

Investigation of drying and wetting effects on response of highly densified tailings to cyclic loadings: Shaking table test results - Fahad Alshawmar; Mamadou Fall (Soil Dynamics and Earthquake Engineering, 2023)

1,2,3-triazenes and 1,2,3-triazoles as antileishmanial, antitrypanosomal, and antiplasmodial agents - Insa Seck; Ismaïla Ciss; Adama Diédhiou; Mamadou Baldé; Seydou Ka; Lalla A. Ba; Samba F. Ndoye; Bruno Figadère; Blandine Seon-Meniel; Generosa Gomez; Sandrine Cojean; Sébastien Pomel; et al. (Medicinal Chemistry Research, 2023)

Assessment of the global toxicity of marine sediments from the Dakar peninsula (Senegal, West Africa) - Amidou Sonko; Dalyal Copin; Patrice Brehmer; Cheikh Diop; Guillaume Constantin De Magny; Mamadou Fall; Yoba Kande; Patricia Moulin; Naby Souleymane Faye; Saliou Faye; Isabelle Linossier; Gaël Le Pennec (Environmental Monitoring and Assessment, 2023)

Behaviour of Backfill Undergoing Cementation Under Cyclic Loading - Imad Alainachi; Mamadou Fall; Muslim Majeed (Geotechnical and Geological Engineering, 2022)

Investigating the metal contamination status from recycling e-waste sites from Dakar, Senegal - Mor Mbodji; Nadia Baskali-Bouregaa; Frédérique Bessueille; Robert Faomowe-Foko; Mamadou Fall; Nicole Gilon (Environmental Science and Pollution Research, 2022)

Gis-Based Assessment of Debris Flow Runout in Kulekhani Watershed, Nepal - Bhuwani Paudel; Mamadou Fall; Bahram Daneshfar (Geotechnical and Geological Engineering, 2021)

A Thermodynamically Consistent Phase Field Model for Gas Transport in Saturated Bentonite Accounting for Initial Stress State - Guanlong Guo; Mamadou Fall (Transport in Porous Media, 2021)

Shear Behaviour of Rock–Tailings Backfill Interface: Effect of Cementation, Rock Type, and Rock Surface Roughness - Kun Fang; Mamadou Fall (Geotechnical and Geological Engineering, 2021)

Effect of groundwater chemistry and temperature on swelling and microstructural properties of sand–bentonite for barriers of radioactive waste repositories - Asmaa Shehata; Mamadou Fall; Christian Detellier; Mohammed Alzamel (Bulletin of Engineering Geology and the Environment, 2021)

A Three-Dimensional Hydro-mechanical Model for Simulation of Dilatancy Controlled Gas Flow in Anisotropic Claystone - Jianxiong Yang; Mamadou Fall; Guanlong Guo (Rock Mechanics and Rock Engineering, 2020)

GIS-based assessment of debris flow hazards in Kulekhani Watershed, Nepal - Bhuwani Paudel; Mamadou Fall; Bahram Daneshfar (Natural Hazards, 2020)

Shear Behavior of the Interface Between Rock and Cemented Backfill: Effect of Curing Stress, Drainage Condition and Backfilling Rate - Kun Fang; Mamadou Fall (Rock Mechanics and Rock Engineering, 2020)

Chemically Induced Changes in the Shear Behaviour of Interface Between Rock and Tailings Backfill Undergoing Cementation - Kun Fang; Mamadou Fall (Rock Mechanics and Rock Engineering, 2019)

State-of-the-Art Modelling of Soil Behaviour Under Blast Loading - Gongda Lu; Mamadou Fall (Geotechnical and Geological Engineering, 2018)

Simulation of Blast Induced Liquefaction Susceptibility of Subsurface Fill Mass - Gongda Lu; Mamadou Fall (Geotechnical and Geological Engineering, 2018)

Coupled Behavior of Cemented Paste Backfill at Early Ages - Alireza Ghirian; Mamadou Fall (Geotechnical and Geological Engineering, 2015)

Characterization of Sensitive Marine Clays by Using Cone and Ball Penetrometers: Example of Clays in Eastern Canada - Athir Nader; Mamadou Fall; Raymond Hache (Geotechnical and Geological Engineering, 2015)

Geotechnical Characterization of Compost Based Biocover Materials - Afshin Khoshand; Mamadou Fall (Geotechnical and Geological Engineering, 2014)

Coupled Modeling of Temperature Distribution and Evolution in Cemented Tailings Backfill Structures that Contain Mineral Admixtures - Di Wu; Mamadou Fall; Si-jing Cai (Geotechnical and Geological Engineering, 2012)

The use of artificial neural networks to predict the effect of sulphate attack on the strength of cemented paste backfill - L. Orejarena; Mamadou Fall (Bulletin of Engineering Geology and the Environment, 2010)

A GIS-based mapping of historical coastal cliff recession - Mamadou Fall (Bulletin of Engineering Geology and the Environment, 2009)